Infeksi Chlamydia Trachomatis pada Penderita Karsinoma Serviks Terinfeksi Human Papilloma Virus (HPV) tipe 16 di RSUP Dr. Sardjito Yogyakarta - Ramayanti, Indri (Syifa'Medika, 2010)
Cervical carcinoma is one of the most common malignant neoplasm amongwomenin developing countries and remains as a major health problem world wide. In Indonesia,the incident of cervical carcinoma are around 180.000 new cases per year or 90-100 nevvcancers among 100.000 communities. Several studies have reported the role of HPV as anSTD agent (Sexually Trasmitted Disease). Cofactor in the HPV infection accelerate up thedevelopment of infection into cancer One of the STD cofactor is co infection with C.trachomatis. Infection ofC. trachomatis is perceived as cofoctor that synergatedwith HPVthroughfree radical mechanism and immune system.The objective of the study is to know the presence of C. trachomatis infection hadpotencyfor being cofactor HPV I 6 in cervical carcinoma patients.Twentylhree sample of cervical smeati cervical carcinoma biopsies and freshtissue obtained from surgerydep, from DR. Sardjito Hospital, Yogtalurta. The DNAisolated of samples were amplified by PCR using primer (E6for-vvard and reversed) fromORF E6 HPV I 6. Sample with positive DNA HPV I 6 was then ampli/ied C. trachomatis genus i ng p ri m er (C C 3 / C C Q from th e s e q uen c e of cry ptic C hl amy dia p I asmid.The research showed thatfrom 23 cases of cervical carcinomawere obtained HPVpositive type 16 with 16 cases (69,5%o). From 16 cases of HPV type 16 positive cervicalcarcinoma, 15 cases were examined to know the presence of C. trachomatis and wereobtained 8 cases (53,j%o) as C. trachomatis positive.